Is XRF core scanning a viable method for coral palaeoclimate temperature reconstructions?. (30th April 2019) - Ellis, Bethany; Grant, Katharine; Mallela, Jennie; Abram, Nerilie
Abstract: The use of X-Ray Fluorescence (XRF) Core Scanning for continuous high-resolution analysis of Sr/Ca in corals is investigated here as a new method for analyzing coral material. Corals are valuable archives for generating high resolution palaeoclimate records of sea surface temperatures of the tropical oceans, but traditional methods of analyzing coral geochemistry involve extensive subsampling and wet chemistry techniques to obtain high precision elemental records. More recent developments of micro-beam techniques have limitations in the length of core that can be scanned at any one time. XRF core scanning provides a fast, non-destructive method of analyzing long sections of coral cores whilst maintaining a high sampling resolution. Here we apply this method to two modern corals, from the Sunda Strait, Indonesia and One Tree Island, Great Barrier Reef Australia. We find that results show that XRF core scanning of corals produce Sr/Ca records that capture the annual cycle, particularly from reef sites with a large sea surface temperature range. Coupled density measurements of the coral skeleton also aid in increasing the utility of XRF measurements obtained from coral material, although difficulties remain in reliably reconstructing interannual temperature variability using XRF Sr/Ca determinations. We recommend that XRF can provide a valuable method of quick and non-destructive screening of coral material, prior to more targeted analysis using traditional destructive geochemical analysis.